Absence of SARS-CoV-2 antibodies in pre-pandemic plasma from children and adults in Vietnam - Chau, NVV; Nhan, LNT; Nguyet, LA; Tu, NTK; Hong, NTT; Man, DNH; Ty, DTB; Nhu, LNT; Yen, LM; Khanh, TH; Quy, DT; Minh, NNQ; et al. (International Society for Infectious Diseases, 2021)
We tested pre-pandemic (2015–-2019) plasma samples from 148 Vietnamese children and 100 Vietnamese adults at high risk of zoonotic infections for antibodies against SARS-CoV-2 nucleocapsid and spike proteins. None was positive. The data thus demonstrated no evidence of prior serological cross-reactivity with SARS-CoV-2 that might explain the low numbers of COVID-19 in Vietnam. No pre-existing cross-reactivity might explain Vietnam success of COVID-19 control.